Atomically Dispersed s‐Block Magnesium Sites for Electroreduction of CO2 to CO. (20th October 2021) - Wang, Qiyou; Liu, Kang; Fu, Junwei; Cai, Chao; Li, Huangjingwei; Long, Yan; Chen, Shanyong; Liu, Bao; Li, Hongmei; Li, Wenzhang; Qiu, Xiaoqing; Zhang, Ning; et al.
Abstract: Atomically dispersed transition metal sites have been extensively studied for CO2 electroreduction reaction (CO2 RR) to CO due to their robust CO2 activation ability. However, the strong hybridization between directionally localized d orbits and CO vastly limits CO desorption and thus the activities of atomically dispersed transition metal sites. In contrast, s‐block metal sites possess nondirectionally delocalized 3s orbits and hence weak CO adsorption ability, providing a promising way to solve the suffered CO desorption issue. Herein, we constructed atomically dispersed magnesium atoms embedded in graphitic carbon nitride (Mg‐C3 N4 ) through a facile heat treatment for CO2 RR. Theoretical calculations show that the CO desorption on Mg sites is easier than that on Fe and Co sites. This theoretical prediction is demonstrated by experimental CO temperature program desorption and in situ attenuated total reflection infrared spectroscopy. As a result, Mg‐C3 N4 exhibits a high turnover frequency of ≈18 000 per hour in H‐cell and a large current density of −300 mA cm −2 in flow cell, under a high CO Faradaic efficiency ≥90 % in KHCO3 electrolyte. This work sheds a new light on s‐block metal sites for efficient CO2 RR to CO. Abstract : Atomically dispersed magnesium atoms embedded in graphitized C3 N4 (Mg‐C3 N4 ) show weak CO adsorption because of nondirectionally delocalized Mg 3 s orbit. Mg‐C3 N4 exhibits a high turnover frequency (TOF) of ≈18 000 hour −1 under a CO Faradaic efficiency ≥90 %. Furthermore, the flow cell fabricated with Mg‐C3 N4 reaches a large current density of −300 mA cm −2 under a CO Faradaic efficiency ≥90 %.